Comparing cognitive fusion and cognitive reappraisal as predictors of college student mental health. Issue 3 (4th May 2019) - Krafft, Jennifer; Haeger, Jack A.; Levin, Michael E.
ABSTRACT: Transdiagnostic cognitive behavioral interventions target different cognitive processes to promote mental health, including cognitive fusion and cognitive reappraisal. Determining the relative impact of cognitive fusion and reappraisal on a range of student mental health concerns could help interventions target psychopathological cognitive processes more effectively. Therefore, this study examined the longitudinal impact of cognitive fusion and reappraisal on mental health and functioning outcomes. A series of hierarchical regression models tested the effects of cognitive fusion and reappraisal in a sample of college students ( n = 339). When controlling for reappraisal and baseline symptoms, fusion predicted distress, depression, generalized anxiety, social anxiety, hostility, academic distress, and student role problems 1 month later. Reappraisal predicted only student role problems longitudinally when controlling for fusion. These results suggest that cognitive fusion is a stronger predictor than reappraisal for a range of student mental health concerns and may be a particularly important target for improving student mental health.